Science education in the Anthropocene: the aesthetics of climate change education in an epoch of uncertainty - Ferguson, Joseph Paul; White, Peta J. (Frontiers in Education, 2023)
We have a responsibility as science educators to work with young people to enact education that enables collective rebalancing of relationships between humans and more-than-humans that are disturbed by human-induced climate change. However, to date, climate change education has not been prioritized in school science at a policy, curricula, classroom and community level, due to an aesthetic which does not sufficiently value climate science or recognize the social impacts of science as part of the discipline. We argue in this conceptual research paper from a pragmatist perspective that an aesthetic shift is required to include science as part of climate change education as a transdisciplinary endeavor that focuses on addressing socio-ecological challenges through student agency and community action. We explore the synergy between science education aesthetics and climate change aesthetics as we advocate for a transformative aesthetics of climate change education. We do so through a process of reflection on and conceptualization of our stories of climate change education in Australia. We propose that such an aesthetic (how we ought to value) should not be considered in isolation but rather that it forms the basis for the ethics (how we ought to conduct ourselves) and logic (how we ought to think) of young people being with us in a community of inquiry in the Anthropocene. We argue that we (teachers and students) ought to conduct ourselves in loving ways toward human and more-than-human kin that necessitates that we think as a community of inquiry to address the challenges of the Anthropocene. In doing so we suggest that we can realize a radical pragmatist meliorism for climate change education that is underpinned by the three normative sciences, the most foundational of which is aesthetics.